Juridical Analysis of the Impact of Economic Contribution and Infidelity on the Division of Marital Assets in Divorce Proceedings - Wulandari, Martina Ayu (PT. Ratu Bilqis Azzahira bekerjasama dengan Fakultas Syariah Universitas Islam Zainul Hasan Probolinggo, 2024)
Chapters 96 and 97 of the Compilation of Islamic Law (KHI) state that widows and widowers, whether due to death or divorce, are entitled to half of the marital property, unless otherwise specified in a marriage agreement. This textual interpretation is often applied rigidly, resulting in potential injustices. This study aims to identify and analyze the effect of family contributions and commitments on the distribution of marital property. Employing a legal approach, this research analyzes judges' considerations in making legal decisions. The findings indicate that family contributions significantly influence judicial decisions on the division of marital assets. For instance, in case number 298/Pdt.G/2022/PA.Kdl, differing contributions from the husband and wife led the judge to deviate from the standard 50:50 division of property. Judges performed contra legem (deviations from the law) by using legal discovery efforts (rechtvinding) with a maslahah approach and considering the legis ratio to ensure justice and fairness. Conversely, in case number 53/Pdt.G/2022/PA.Gtlo, a party's violation of family commitments was not factored into the judge's decision to reduce their share of the marital property. Traditionally, infidelity could affect the division of joint property. It is suggested that judges consider traditional laws to potentially reduce the share of those violating family commitments, ensuring more equitable outcomes